COLLABORATIVE GOVERNANCE DALAM PELAYANAN ADMINISTRASI KEPENDUDUKAN BAGI MASYARAKAT MISKIN DI DESA KESAMBEN KULON - Mareta Ryarsa Hanyfa; Eni Rustianingsih (Halu Oleo University, 2024)
The government must be able to overcome problems related to population administration in order to provide public services, especially in rural areas. One of the communities in Gresik Regency that has problems accessing population administration is Kesamben Kulon Village, especially for the poor. The Non-Governmental Organization Women's Group and Life Resources intervened through the INKLUSI Program from one of the 6 priority issues, namely legal identity guarantees for marginalized communities to overcome population administration problems faced by the poor in Kesamben Kulon Village. This is done through collaborative governance with the Population and Civil Registration Service of Gresik Regency. This study used a descriptive method with a qualitative approach. The focus of this study is to use the collaborative governance theory according to Ansell and Gash (2007:228) which emphasizes Face Dialogue, Trust Building, Commitment to The Process, Shared Understanding, and Intermediate Outcome. The results of the analysis of this study show that the five indicators of the collaborative governance process by Ansell and Gash (2007:228) have been carried out by each stakeholder.